Buildings in Iraq (مجلة المنصور, 2022)
The study is concerned with building (green and eco-friendly) because of the significant impact on reducing energy and water consumption and minimize damage to the environment of the establishment of the various buildings and running and providing a smart and healthy modern buildings for occupants with interest thermal insulation and acoustic good, achieving a balance and complementarily between man and the environment surrounding it through the high efficiency of the use of local resources and deal effectively with the climate and geographic and social environment in Iraq and achieve the appropriate requirements of the users of the building while sustainable preserving the rights of future generations.The main objectives of this study are as follows:1. Prepare a research paper contributes to the establishment of a special design, implementation and maintenance of sustainable buildings in Iraq, an Iraqi Specification.2. Provide thermal insulation and this will contribute to solving the fundamental problems in Iraq. 3. Design a sustainable building commensurate with the climate and environment of Iraq, its needs and its implementation on the ground if funding is available.The building was designed according to the specifications of green buildings, taking into account the orientation of the building as the site of Iraq in the northern hemisphere and the prevailing winds seasonally and by climatic and environmental conditions of Baghdad city.